Digital Public Relations as a Mechanism for Managing Corporate Reputation in the Digital Age: An Analytical Approach - Neche, Azouz (Journal of Ecohumanism, 2026)
This article examines the role of digital public relations as a strategic tool for managing corporate reputation in the digital age. It highlights the fundamental shift from traditional, one-way models to interactive models that rely on social media platforms, websites, blogs, and modern digital communication tools. The article emphasizes that digital reputation has become one of the most important intangible assets for an organization, directly impacting customer trust, loyalty, and competitiveness in the digital market.The article also explains how digital public relations contributes to monitoring content published about the organization, managing negative feedback, and enhancing a positive image by disseminating credible and valuable content that reflects the organization's principles and values, thereby increasing its credibility with the public. It further highlights the importance of digital reputation management strategies and concludes that digital public relations is no longer merely a means of disseminating information, but has become a fundamental pillar for building and managing corporate reputation and fostering trust and credibility in the changing and complex digital environment. The study also affirms that integrating these strategies with digital analytics tools enables organizations to improve their communication performance and achieve their corporate goals more effectively.